Similar dietary regulation of IGF-1- and IGF-binding proteins by animal and plant protein in subjects with type 2 diabetes - Schüler, Rita; Markova, Mariya; Osterhoff, Martin A.; Arafat, Ayman; Pivovarova, Olga; Machann, Jürgen; Hierholzer, Johannes; Hornemann, Silke; Rohn, Sascha; Pfeiffer, Andreas F. H. (European journal of nutrition, 2021)
Increased animal but not plant protein intake has been associated with increased mortality in epidemiological studies in humans and with reduced lifespan in animal species. Protein intake increases the activity of the IGF-1 system which may provide a link to reduced lifespan. We, therefore, compared the effects of animal versus plant protein intake on circulating levels of IGF-1 and the IGF-binding proteins (IGFBP)-1 and IGFBP-2 over a 6-week period. Thirty seven participants with type 2 diabetes consumed isocaloric diets composed of either 30% energy (EN) animal or plant protein, 30% EN fat and 40% EN carbohydrates for 6 weeks. The participants were clinically phenotyped before and at the end of the study. Both diets induced similar and significant increases of IGF-1 which was unaffected by the different amino acid compositions of plant and animal protein. Despite improvements of insulin sensitivity and major reductions of liver fat, IGFBP2 decreased with both diets while IGFBP-1 was not altered. We conclude that animal and plant protein similarly increase IGF-1 bioavailability while improving metabolic parameters and may be regarded as equivalent in this regard.